Internal Macroscopic Anatomy and Electrical Evaluation of the Bradypus variegatus Heart - Albuquerque, Priscilla Virgínio de; Ferri, Rinaldo Cavalcante; Braz, Richelle da Silva; Mesquita, Emanuela Polimeni de; Torres, Sandra Maria de; Tschá, Mauricéa do Carmo; Amorim Júnior, Adelmar Afonso de; Amorim, Marleyne José Afonso Accioly Lins (Acta Scientiae Veterinariae, 2021)
Background: The Bradypus variegatus species presents peculiar anatomophysiological properties and many aspects of its organic systems still need to be clarified, especially regarding the cardiovascular system, given its participation in vital activities. Disorderly anthropic action has had drastic consequences in sloth populations and the need to treat sick and injured animals is increasingly common. To this end, the importance of knowing its characteristics is emphasized. Therefore, this study proposed to describe the internal macroscopic structures of the sloth’s heart, as well as to measure the ventricular walls and indicate the electrical activity of the organ. Materials, Methods and Results: For the dissections, 15 Bradypus variegatus cadavers were used (1 young female, 9 adults females and 5 adult males) belonging to the Área de Anatomia of the Departamento de Morfologia e Fisiologia Animal (DMFA), Universidade Federal Rural de Pernambuco (UFRPE), Recide, PE, Brazil. After they were fixed and preserved, the specimens received a midsagittal incision in the chest, followed by soft tissue folding and removal of ribs to access the heart. The organ was derived from the cavity and sectioned sagittal medially to identify its internal anatomy. Ventricular walls and interventricular septum were measured with a steel caliper (150 mm / 0.02 mm). An electrocardiogram was performed to determine the electrical profile on 5 healthy B. variegatus sloths, living under semi-livestock conditions at the Recife Zoo, PE, Brazil. The electrodes were taken from the regions, scapular and glutes of the animals that were called hugging a keeper during the procedure, carried out in the Zoo itself, using a portable device. Based on the data obtained, sloths have cardiac chambers separated by septa, however between atria and ventricles, in both antimeres, there are atrioventricular ostia, where valves are found, consisting of 3 valves on the right and 2 on the left. The atria are practically smooth inside and have their cavity enlarged by the atria, the right being larger than the left, these having a greater amount of pectineal muscles in relation to the atria. The ventricles have trabeculae and papillary muscles, 3 on the right and 2 on the left. These muscles hold the tendinous chords that connect the valves. The existence of trabeculae marginal septum was not evidenced. The thickness of the wall of the left ventricle, as well as that of the interventricular septum, proved to be greater than the thickness of the wall of the right ventricle, regardless of the age or sex of the animals. Based on the electrocardiographic recordings, the sloths presented sinus rhythm, with a heart rate between 67 and 100 bpm. The electrical axis ranged from -60º to -90º. The P wave is smoother than the QRS complex. While the S-T segment was classified as isoelectric. The T wave was shown to be + and predominantly > or = at 25% of the S wave, which characterized an rS type QRS deflection in both females and males. Discussion: The general characteristics of the cardiac chambers in sloths are similar to those observed in other domestic and wild mammals. However, the presence of pectineal muscles associated with the atria and auricles differs from that observed in mammals such as the paca and raccoon and in birds such as the ostrich, which have trabecular structures in these cavities. The number of valves in sloths is equal to the anteater. However, it has a marginal trabeculae septum, not seen in Bradypus variegatus. According to the electrocardiographic findings, the rhythm was sinus, but much lower than that observed in the capuchin monkey, which also maintains arboreal habits. Keywords: Xenarthra, common sloth, internal anatomy, heart, electrocardiogram. Descritores: Xenarthra, preguiça-comum, anatomia interna, coração, eletrocardiograma.